Readiness of Indonesian pre-service science teachers for society 5.0 - Irwandani, Irwandani; Suyatna, Agus; Haenilah, Een Yayah; Maulina, Dina (Journal of Education and Learning (EduLearn), 2024)
This research aimed to assess the readiness of Indonesian pre-service science teachers by examining their perceptions of impending challenges, desired competencies, and anticipated instructional methodologies in preparing for the challenges of Society 5.0. Using a quantitative survey research methodology, 884 pre-service science teachers from 16 universities were surveyed. The research instrument's validity and reliability were assessed utilizing the Rasch model. Inferential statistics were employed to assess the readiness of pre-service science teachers for future challenges, taking into account their backgrounds. The test outcomes showed the Cronbach's Alpha coefficient reached 0.92, is deemed "excellent", affirming the instrument's high reliability. The findings of the study revealed that the majority of teachers share a consistent perception of future challenges and recognize the importance of mastering 21st-century skills, particularly critical thinking, creative thinking, communication, and collaboration. However, respondents believe that the current learning process does not adequately train these skills. They expressed a desire for an alternative learning method that can enhance their skills while accommodating their diverse backgrounds, including place of residence, economic background, and technological proficiency. Further research is needed to identify alternative teaching methods that can effectively foster these abilities in diverse backgrounds.